2018
DOI: 10.1053/j.gastro.2018.08.028
|View full text |Cite
|
Sign up to set email alerts
|

An Inhibitor of GSK3B and HDACs Kills Pancreatic Cancer Cells and Slows Pancreatic Tumor Growth and Metastasis in Mice

Abstract: In studies of PDAC cells and 2 mouse models of PDAC, we found a dual inhibitor of GSK3B and HDACs (Metavert) to induce cancer cell apoptosis, reduce migration and expression of stem cell markers, and slow growth of tumors and metastases. Metavert had synergistic effects with gemcitabine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 55 publications
1
53
0
Order By: Relevance
“…These morphological changes in tumor cells induced by GSK3β inhibition coincided with the disruption of pathways that are mediated sequentially by focal adhesion kinase (FAK), guanine nucleotide exchange factors (GEFs), Rac1 and c-Jun N-terminal kinase (JNK) (reviewed in [15]). Other studies have also demonstrated the pro-invasive nature of GSK3β in colorectal, pancreatic and breast cancer cells via the modulation of cytoskeletal microstructures and cytokine-mediated extracellular matrix degradation [44,64,69]. Together, these studies provide evidence that GSK3β enhances the process of tumor invasion and probably also that of metastatic spread.…”
Section: Gsk3β and Tumor Invasionmentioning
confidence: 66%
See 1 more Smart Citation
“…These morphological changes in tumor cells induced by GSK3β inhibition coincided with the disruption of pathways that are mediated sequentially by focal adhesion kinase (FAK), guanine nucleotide exchange factors (GEFs), Rac1 and c-Jun N-terminal kinase (JNK) (reviewed in [15]). Other studies have also demonstrated the pro-invasive nature of GSK3β in colorectal, pancreatic and breast cancer cells via the modulation of cytoskeletal microstructures and cytokine-mediated extracellular matrix degradation [44,64,69]. Together, these studies provide evidence that GSK3β enhances the process of tumor invasion and probably also that of metastatic spread.…”
Section: Gsk3β and Tumor Invasionmentioning
confidence: 66%
“…To date, the tumor-promoting functions of deregulated GSK3β have been reported in 25 cancer types from various organs and tissues across the body ( Table 1 ) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ...…”
Section: Tumor-promoting Roles Of Gsk3β In Various Cancer Typesmentioning
confidence: 99%
“…Such a relationship was also revealed in preclinical experiments on novel molecules, providing hits for further research. Metavert, an inhibitor of glycogen synthase kinase 3β and histone deacetylases, could normalize the glucose metabolism of pancreatic cancer cells and transform M2-like TAMs to the anticancer M1 phenotype in mouse models [127].…”
Section: Metabolic Crosstalk Within the Microenvironmentmentioning
confidence: 99%
“…8 A recent study elucidated that glucose metabolism is involved in pancreatic tumors and that inhibition of glycogen synthase kinase 3 beta retards cancer progression in mice. 9 Alterations in metabolic protein expression and associated post-translational modification (PTM) effects may underlie the necessary adaptive changes seen in cancer cell metabolism. 10 Lysine acetylation (Kac) is an important reversible and dynamic protein PTM.…”
Section: Introductionmentioning
confidence: 99%